Clinical Confidence, Certification, and Connectedness: Impact of a Journal Club for Inpatient Psychiatry Faculty - David S. Im; Andrea Brelje; Christina Raghunandan; Laura Stchur; Angela Lyden; Allison Hong; Lindsay A. Bornheimer (Journal of Medical Education and Curricular Development)
INTRODUCTION Inpatient psychiatry faculty manage complex clinical, administrative, and legal issues amid increasing mental health service utilization rates, limiting time for (1) focusing on lifelong learning and (2) connecting. We examined the impact of a monthly journal club on inpatient psychiatry faculty's (1) confidence that their practice is evidence informed, (2) stress related to board recertification, and (3) sense of connectedness with peers. METHODS We employed a primarily qualitative approach using semi-structured interviews and brief survey questions to elicit input from inpatient psychiatry faculty at an academic medical center on their experience participating in a monthly journal club, including perceived changes in one's practice of evidence-based medicine, recertification stress, and connectedness with peers. RESULTS Thirteen faculty who participated in the journal club responded to at least one survey or interview. Many faculty reported feeling more confident that their clinical practice was evidence informed, less stressed about board recertification, and more connected to peers at 6 and 12 months following the commencement of the journal club. Following in-person attendance, video-based learning (an innovative method of participating in the journal club) was found to be the second most preferred method of participation among respondents. All respondents noted that the journal club was a valuable use of their time and enjoyable. CONCLUSION A monthly journal club has the potential to increase hospital psychiatry faculty confidence in evidence-based clinical practice, reduce board recertification stress, and improve sense of peer connectedness. Future research should examine the journal club experience and impact among a larger number of faculty and incorporate additional measures of learning outcomes.